2001
DOI: 10.1046/j.1524-4741.2001.99070.x
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Cytologic Imprints of Stereotactically Guided Core Needle Biopsies of the Breast in the Management of Patients with Mammographic Abnormalities

Abstract: Between 1995 and 1996, 96 consecutive patients with nonpalpable breast lesions detected by abnormal mammogram underwent core needle biopsies under stereotactic guidance at Johns Hopkins Bayview Medical Center. The cytologic diagnoses rendered on touch imprints and the histopathologic diagnoses made on the core needle biopsies were retrospectively reviewed to ascertain the accuracy and the validity of this procedure. These imprints were made of the cores as on-site evaluation in order to assist the radiologist.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
2
12
2
1
Order By: Relevance
“…In TIC, the core is rubbed onto a slide and the resulting 'touch imprint' is stained according to Papanicolaou or Diff-quick [13]. Frozen section histology is a regular frozen section, performed on a CNB specimen allowing for a quick histological diagnosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…In TIC, the core is rubbed onto a slide and the resulting 'touch imprint' is stained according to Papanicolaou or Diff-quick [13]. Frozen section histology is a regular frozen section, performed on a CNB specimen allowing for a quick histological diagnosis [14].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, TP cytology has been evaluated as an improved means for offering same-day diagnosis for CNB. It has been shown that the sensitivity and specificity of TP cytology range from 75% to 95% and from 95% to 98%, respectively [56][57][58][59]. The frequency of inadequate TP cytology varies widely, from 0 to 29%, and is similar to that of FNAB [56,[59][60][61].…”
Section: Breast Core Needle Biopsiesmentioning
confidence: 99%
“…In studies on CWC the sensitivity and specificity varied from 85% to 89% and 72% to 98%, respectively, while the inadequate rate varied from 7% to 42% [1,2]. Studies on TIC showed variable results as well [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 95%